2021
DOI: 10.3390/f12111474
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Genetic Variation in Resistance to Pinewood Nematode (Bursaphelenchus xylophilus) in Pinus radiata D. Don Half-Sib Families

Abstract: Full understanding and control of pine wilt disease (PWD) is a work in progress and breeding for disease resistance constitutes an essential management strategy for reducing its impact, as evidenced by advanced breeding programs in countries such as Japan. Since Pinus radiata is one of the most commercially relevant species in northern Spain, we designed a study to assess genetic variation in susceptibility to this pathogen using 44 P. radiata half-sib families from the Galician breeding program. Three Bursaph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
0
7
0
2
Order By: Relevance
“…We obtained occurrence point data for B. xylophilus from multiple sources, including the Centre for Agriculture and Bioscience International (CABI), the Global Biodiversity Information Facility (GBIF) (the last time to browse CABI was November 13, 2022, and to browse GBIF was November 8, 2022), Announcement No. 6 of 2022 issued by the State Forestry and Grassland Administration of China, and publicly available studies [ 30 , 39 41 ]. For locations mentioned in publicly available studies without latitude and longitude data, we used Google Earth (version 7.1) to obtain GPS coordinates.…”
Section: Methodsmentioning
confidence: 99%
“…We obtained occurrence point data for B. xylophilus from multiple sources, including the Centre for Agriculture and Bioscience International (CABI), the Global Biodiversity Information Facility (GBIF) (the last time to browse CABI was November 13, 2022, and to browse GBIF was November 8, 2022), Announcement No. 6 of 2022 issued by the State Forestry and Grassland Administration of China, and publicly available studies [ 30 , 39 41 ]. For locations mentioned in publicly available studies without latitude and longitude data, we used Google Earth (version 7.1) to obtain GPS coordinates.…”
Section: Methodsmentioning
confidence: 99%
“…2018, Brockerhoff 2009, Brockerhoff et al 2023). Finally, although Brockerhoff (2009) suggested that radiata pine appeared to be resistant to the nematode B. xylophilus Steiner & Buhrer, that is spread by bark beetles, it has been found, after inoculation, to cause pine wilt disease in radiata pine in Spain (Menéndez-Gutiérrez et al . 2021).…”
Section: Overseas Threats To Radiata Pine In New Zealandmentioning
confidence: 99%
“…Other secondary bark beetles known to attack weakened radiata pine outside New Zealand, and which might become vectors of PPC if this fungus appeared in New Zealand, are Orthotomicus erosus Wollaston, Pityophthorus pubescens Marsh., Dendroctonus valens Leconte and Tomicus pineperda L. (Bezos et al 2018, Brockerhoff 2009, Brockerhoff et al 2023. Finally, although Brockerhoff (2009) suggested that radiata pine appeared to be resistant to the nematode B. xylophilus Steiner & Buhrer, that is spread by bark beetles, it has been found, after inoculation, to cause pine wilt disease in radiata pine in Spain (Menéndez-Gutiérrez et al 2021). These authors found that it should be possible to breed trees resistant to these nematodes.…”
Section: Invasive Wood-boring and Bark Beetlesmentioning
confidence: 99%
“…First, PWNs were suspended in water at a concentration of 1000 PWNs/mL (as described above), and the inoculated hosts were 3-4-year-old Pinus koraiensis (purchased from Liaoning, China, with an average height of 40 cm and an average thickness of 1.5 cm and cultured in a greenhouse for 30 days before the experiment). The inoculation method was as follows 26,27 : the part with fewer needles of each plant was selected, and longitudinal incisions were made with a sterile blade. A piece of sterile absorbent cotton was inserted, and a pipette gun was used to transfer 1 mL of nematode suspension (1000 PWNs) into the absorbent cotton.…”
Section: Prevention and Treatment Of Pwdmentioning
confidence: 99%